PAST AND PRESENT EDUCATION IN UZBEKISTAN - Mirzayeva Zilola Mirjon qizi; Zubaydova Nilufar Negmatullayevna; Azzamova Nigora Rajabboyevna (TADQIQOTLAR.UZ, 2024)
Abstract:  This  article  provides  not  only  information  about  past  and  present education but  also differences  between last  and current education in Uzbekistan.  It describe research in the field of education and favorable opportunities. Besides this school textbooks are explained as examples.